Effects of Service Quality, Food Quality, and Price Fairness Customer Satisfaction at Japanese restaurant 3 Wise Monkeys, Jakarta - Rara Wilis Setiawati; Innocentius Bernarto (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the positive influence of service quality, price fairness, and food quality positive effects on customer satisfaction. The target population of the study is all customers of Japanese restaurant 3 Wise Monkeys Jakarta. As for determining the sample using purposive sampling techniques. The specified sample number is 200 samples that are customers of Japanese restaurant 3 Wise Monkeys. The data is collected by distributing questionnaires. The data was analyzed using the partial least square-structural equation modeling (PLS-SEM) model. The results showed that service quality, price fairness, and food quality had a positive influence on customer satisfaction at Japanese restaurant 3 Wise Monkeys.